Comparison Between SAW and TOPSIS Methods in Selection of Broiler Chicken Meat Quality - Adi, Pungky Tri Kisworo; Sugiharti, Endang; Alamsyah, Alamsyah (Universitas Negeri Semarang, 2018)
Decision support system is a system that can assist semi-structured and unstructured decision making, in which no one knows exactly how decisions should be made. Broiler Chicken farm production is growing very rapidly along with the increasing market demand for Broiler Chicken. Broiler Chickens have fast growth in a relatively short time. The purpose of this research is the selection of chicken meat quality by applying comparison of SAW and TOPSIS method. The variables used are age, ration conversion, weight of chicken weight, and water consumption. The system is created using PHP framework Code Ignitier and database MySQL using waterfall method. That is analyze the user needs on the system, do the database design, by doing a coding and testing the system whether it is what is expected. The result of this research is the application of comparison between SAW and TOPSIS method each consist of 5 criteria. Comparison of these algorithms can facilitate the breeders in choosing a good quality broiler chicken meat.The results of the best farmer recommendation according to comparative method of SAW and TOPSIS. In SAW method of breeder 1 The biggest value is at V2 = 0,341, so alternative A2 is alternatives chosen as good alternative. Breeder 2 The biggest value is at V3 = 0.033, so alternative A3 is the alternative chosen as a good enough alternative. Breeder 3 The biggest value is at V1 = 0.005, so alternative A1 is the alternative chosen as an excellent alternative. Topsis Method of Breeders 1 is the largest valueÂ at V2 = 9.98, so alternative A2 is the alternative chosen as a good alternative. Breeder 2 is the biggest value at V3 = 0.372, so alternative A3 is the alternative chosen as a good enough alternative. Breeder 3 is the biggest value at V3 = 0.982, so alternative A3 is the alternative chosen as a good enough alternative. This system uses only 5 criteria, it would be nice if you add other criteria that support the selection of broiler chicken meat quality.